Towards a ‘Narrow-Scope Epistemology’: Rationality and Situatedness in Kuhn, Lakatos and Feyerabend - Ortega Caro, Cristian Enrique (2025)
Traditional epistemology has approached the scientific phenomenon as a logical-methodological problem, primarily focusing on issues such as the truth/error dispute, the structure of theories, the empirical reducibility of theoretical concepts, and the progress or accumulation of knowledge. In contrast, the sociological approach to science has examined how this same phenomenon can be understood through its socio-historical context and microscopic elements. Building on this tension, this paper presents an analytical framework for interpreting scientific practices as a problem of “epistemic subjectivity”. This model shifts from a historical-structural interpretation of scientific activity to a situated interpretation of it. Drawing on the work of Kuhn, Feyerabend, and Lakatos, the paper explores what can be termed a micro-epistemology or a “narrow-scope epistemology” that aims to recontextualize scientific rationality as dynamic practices that relocate themselves and overlap with one another according to diverse interests and socio-technical levels.